A Multimethod Analysis of Thyroid Hormone Profiles and Growth Indicators in Pediatric β-Thalassemia Major: A Study in Indonesia - N. Herdata, Heru; Fiftiara, Finda; Destianti, Eka; Purba, Quranayati (Lembaga Teewan Journal Solutions, 2026)
Children with thalassemia are at increased risk of growth impairment and endocrine dysfunction, including thyroid abnormalities. However, the relationship between thyroid function and stunting remains unclear. This cross-sectional study included 51 children with confirmed thalassemia. Growth status was assessed using height-for-age Z-score (HAZ) and percentage height deficit relative to mid-parental target height (Mid-TPG), while thyroid function was evaluated by measuring serum thyroid-stimulating hormone (TSH) and free thyroxine (FT4). Data were analyzed using Pearson or Spearman correlation, multivariable linear regression, locally estimated scatterplot smoothing (LOESS), generalized additive models (GAM), and k-means clustering. No significant associations were found between thyroid hormone levels and either HAZ or height deficit in multivariable analyses (all p > 0.05). FT4 showed a weak positive correlation with HAZ (ρ = 0.265), although it was not statistically significant (p = 0.06). LOESS and GAM demonstrated limited explanatory power. K-means clustering identified three distinct growth phenotypes with significant differences in HAZ and height deficit (p < 0.001), whereas TSH and FT4 levels did not differ across clusters. These findings suggest that thyroid hormone levels are not significantly associated with stunting severity in children with β-thalassemia major, highlighting the multifactorial nature of growth impairment and the need for further investigation to support targeted intervention strategies.